Likelihood of missed and recurrent adenomas in the proximal versus the distal colon - Laiyemo, Adeyinka O. (2011)
BACKGROUND: Colonoscopy may be less efficacious in reducing colorectal cancer mortality in the proximal as compared with the distal colon. A greater likelihood for missed and recurrent adenomas in the proximal colon may contribute to this phenomenon. OBJECTIVE: To examine whether a proximal adenoma is associated with the risk and location of missed and recurrent adenomas. DESIGN: Prospective SETTING: Polyp Prevention Trial PARTICIPANTS: 1,864 patients with adenoma at baseline underwent a follow-up colonoscopy four years later (adenoma recurrence). Of these, 1,731 underwent a clearing colonoscopy one year after the baseline examination (missed adenoma). MEASUREMENTS: Association of baseline adenoma location with the risk and location of adenomas found at colonoscopy performed one year and four years later. RESULTS: At the year 1 colonoscopy, 598 (34.6%) patients had an adenoma (missed adenoma). Compared with those with distal only adenoma at baseline, patients with proximal only adenoma at baseline were more likely to have any missed adenoma (relative risk (RR)=1.28; 95% confidence interval (CI): 1.09–1.49) and proximal only missed adenoma (RR=2.05; 95%CI: 1.49–2.80). At the year 4 colonoscopy, 733 (39.3%) patients had an adenoma recurrence. Patients with baseline proximal only adenoma were more likely to have any adenoma recurrence (RR=1.14; 95%CI: 1.00–1.31) and proximal only adenoma recurrence (RR=1.52; 95%CI: 1.15–2.02). Sensitivity analyses involving missed adenomas did not materially affect the risk or location of recurrent adenomas at year four colonoscopy. LIMITATION: Lesions may still be missed with repeated colonoscopies. CONCLUSIONS: Missed and recurrent adenomas are more likely to be in the proximal colon.